Pengaruh Profitabilitas, Struktur Modal, dan Likuiditas terhadap Nilai Perusahaan dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Yuli Ermawati; Edo Tri Nahendra Agustino (Jurnal Riset Akuntansi, 2025)
This study aims to analyze the influence of Profitability, Capital Structure, and Liquidity on Firm Value with Firm Size as a moderating variable. Employing a quantitative approach using purposive sampling method, the study includes 26 food and beverage industry companies listed on the Indonesia Stock Exchange (BEI) from 2021 to 2023. The research tests the effects of independent variables on dependent variables and through moderating variables. Hypothesis testing results indicate a significant positive effect of profitability on firm value, while no significant influence is found between capital structure, liquidity, and firm value. Moderation testing shows that firm size moderates the impact of liquidity on firm value, but not yet for profitability and capital structure.